2021
DOI: 10.1186/s12970-020-00406-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-fat, lactose-free and leucine-enriched chocolate cow milk prototype: A preliminary study on sensorial acceptability and gastrointestinal complaints following exhaustive exercise

Abstract: Background Chocolate milk has gained recent scientific support as a recovery drink. However, it is known that high exercise-demand triggers gastrointestinal discomfort which continues post-exercise, thereby hindering this nutritional strategy. In addition, those who are lactose intolerant cannot benefit from a milk-based beverage. Thus, the aim of this preliminary study was to develop a low-fat, lactose-free, and leucine-enriched chocolate cow milk prototype (CML) representing nutrition-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…However, for all postexercise and postfluid ingestion time of measurements, no differences were identified among categories or time of measurement. The report of very mild symptoms after milk ingestion postexercise, and no significant differences among beverages, agrees with Karp et al (2006), da Silva et al (2021 and Russo et al (2021), which show very low severity in reported GI symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…However, for all postexercise and postfluid ingestion time of measurements, no differences were identified among categories or time of measurement. The report of very mild symptoms after milk ingestion postexercise, and no significant differences among beverages, agrees with Karp et al (2006), da Silva et al (2021 and Russo et al (2021), which show very low severity in reported GI symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…The developers proposed a lactose-free "ready-to-eat" product that was tested on a group of soccer players. The findings suggest that CML tasted good and was well tolerated by athletes in this study [114]. This suggested that CML could be an alternative sports drink that would provide post-workout energy recovery while avoiding discomfort for athletes with lactose intolerance.…”
Section: Functional Food For Athletesmentioning
confidence: 55%
“…Balducci et al [53] showed that long-term sustained aerobic exercise and resistance exercise with moderate-to-low intensity could reduce the expression of inflammatory cytokines (such as IL-1β and TNF-α), while increase the expression of antiinflammatory cytokines (such as IL-4 and IL-10) in the body. Meanwhile, according to previous reports, especially in partial professional athletes, the acute and vigorous exercise might induce the transient gastrointestinal symptoms (such as nausea, diarrhea, gastrointestinal bleeding, and so on) [54][55][56]. However, the participation in normal moderate intensity exercise is considered to resist intestinal inflammatory diseases, and the gastrointestinal disorders usually do not occur after the moderate intensity exercise, which might be associated with the involvement of GM in regulation [57].…”
Section: Long-term Chronic Moderate-to-low Intensity Exercisementioning
confidence: 99%